Perencanaan Anggaran Operasional untuk UMKM Meubel Citra - intan permata kasih; Markoni; Neneng Miskiyah (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2024)
This research aims to determine the planning process through preparing the operational budget at Meubel Citra, a micro, small and medium enterprise (MSME). The method used is a quantitative descriptive approach, with data collection through direct interviews with company owners and observation of operational activities at Meubel Citra. The data collected is analyzed to identify the types of costs incurred by the company and to understand usage patterns based on financial records for the last five years. The research results show that Citra Meubel has never implemented an operational budget before. This condition has an impact on difficulties in monitoring and managing the company's financial condition effectively, which in turn affects the company's performance and profits. Therefore, this research emphasizes the importance of implementing operational budgets to increase company efficiency and effectiveness in managing expenses. The operational budget is also expected to help in formulating strategic policies, including determining appropriate selling prices based on recorded production and operational costs. It is hoped that the preparation of the operational budget at Meubel Citra can be the first step in improving better financial governance and supporting sustainable growth for MSMEs in the furniture industry sector.